A Study on Air Traveller’s Satisfaction of Service Quality for Jaipur International Airport (JIA) - Dr. Manoj Kumar; Krishan Kant Meena, (Indian Journal of Management and Language (IJML), 2024)
This paper explores on service quality of an Jaipur International airport, which is more influenced on the passenger satisfaction. Measuring and improving service quality has become an important. The quality of airport services for passenger is investigated in this paper using Airport Council international Airport service Quality (ASQ) method. The data were collected through structured questionnaire addressed to departing and arrival passengers. Passengers expressed their perceptions according to an ordinal verbal scale about some service factors concerning aspects such as Check-In, security, Airport facilities, access, and arrival services etc. We propose an ordered ACI ASQ model with the aim to investigate on the result from the analysis has suggested that all the dimensions of service quality influences the passenger satisfaction. The information endowed with the study can be used for designing the marketing strategies to improve the passenger satisfaction in aviation industry.